Positive Alpha-defensin at Reimplantation of a Two-stage Revision Arthroplasty Is Not Associated with Infection at 1 Year. Issue 7 (July 2019) - Samuel, Linsen T.; Sultan, Assem A.; Kheir, Matthew; Villa, Jesus; Patel, Preetesh; Parvizi, Javad; Higuera, Carlos A.
Abstract: Background: Diagnosing periprosthetic joint infection (PJI) represents a challenge that relies on multiple clinical and laboratory criteria that may not be consistently present. The synovial alpha-defensin-1 (AD-1) test has been shown to correlate accurately with the Musculoskeletal Infection Society (MSIS) criteria for the diagnosis of PJI, however, its association with persistent PJI has not been elucidated in the setting of patients receiving antibiotic spacers during second-stage reimplantation. Applying a Delphi-based consensus to define successful eradication of PJI offers an opportunity to test the utility of AD-1 in this setting. Questions/purposes: (1) Can the AD-1 test determine whether infection has been controlled using the Delphi criteria for persistent PJI as a surrogate for infection eradication during two-stage revision for PJI treatment with a spacer? (2) How does the performance of the AD-1 test compare with the MSIS criteria? Methods: This was a multicenter analysis of retrospectively collected data on patients who underwent a two-stage revision arthroplasty between May 2014 and July 2016. We included patients who had a previously confirmed PJI and received a cement spacer, underwent the second stage, had MSIS criteria data and a synovial fluid AD-1 test, and had a minimum followup of 1 year. We were unable to determine for all study sites how many patients had the test but did not meet all the criteria and so could not be studied; however, we were able to identify 69 patients (43 knees, 26 hips) who met all criteria. During the period in question, indications for use of AD-1 varied by surgeon; however, during that time, in general if a surgeon ordered it as part of the initial workup, the test would have been repeated before the second-stage reimplantation procedure. To assess the validity of AD-1 against persistence of PJI criteria at 1 year, the following were calculated using the Delphi criteria for persistent PJI as the gold standard: sensitivity, specificity, positive and negative predictive values, accuracy, and area under the curve (AUC) with 95% confidence intervals (CIs). Concordance index (c-index) and its Wald 95% CI with receiver operating characteristic (ROC) curve were calculated in relation to Delphi criteria for persistent PJI using AD-1 and then MSIS criteria. The two c-indices of AD-1 and MSIS were compared using the DeLong nonparametric approach. Results: The AD-1 test showed poor sensitivity (7%; 95% CI, 0.2–34), and poor overall accuracy (73%; 95% CI, 60–83; AUC = 0.5; 95% CI, 0.3–0.6) in detecting infection eradication at 1 year. The c-index for AD-1 versus Delphi criteria for persistent PJI was 0.519 (95% CI, 0.44–0.60), and the c-index for MSIS criteria versus Delphi criteria for persistent PJI was 0.518 (95% CI, 0.49–0.54), suggesting the weak diagnostic abilities of these models. The contrast estimate between MSIS criteria and AD-1 were not different from one another at -0.001 (95% CI%, -0.09 to 0.09; p = 0.99). Conclusions: We found that a positive synovial fluid AD-1 test correlated poorly with the presence of persistent infection 1 year after two-stage revision arthroplasty for PJI. For this reason, we recommend against the routine use of AD-1 in patients with cement spacers, until or unless future studies demonstrate that the test is more effective than we found it to be. Level of Evidence: Level IV, diagnostic study.